The Effect of Product Quality on Customer Loyalty through Consumer Satisfaction and Company Reputation - Alfionita, Hilda; Harmadi, Harmadi; Selliandro, Octano; Soesilo, Primidya (LifeSciFi, 2025)
This study examines the influence of product quality on customer satisfaction, corporate reputation, and its impact on customer loyalty among active participants of PT. Taspen (Persero) in Indonesia. It employs an explanatory research design with a sample of 240 respondents selected using a random sampling method. Sampling was conducted at five branch offices with the largest number of active participants. The data analysis method used was Structural Equation Modelling with Partial Least Squares (SEM-PLS). The findings reveal that product quality has a positive and significant effect on customer satisfaction. However, product quality does not significantly affect corporate reputation. Additionally, both customer satisfaction and corporate reputation have a significant positive effect on customer loyalty. This indicates that when customers are satisfied and perceive a good corporate reputation, they are more likely to remain loyal and continue using services. The study highlights the importance of customer satisfaction as a key driver of loyalty, even more than corporate reputation in this context. These results provide valuable insights into improving service strategies.